Pengaruh Penggunaan Hypermedia Flipbook Terhadap Minat dan Hasil Belajar Siswa Pada Materi Sistem Ekskresi Manusia - Hakim, Miftahul (INDIGENOUS BIOLOGI : JURNAL PENDIDIKAN DAN SAINS BIOLOGI, 2023)
Learning media is very important in the world of education, one of which is by utilicinhhg ICT (Information and Communication Technology), namely flipbooks. The emergence of the problem of learning media that is less varied in schools makes students less active and feel bored in the learning process. This study aims to determine the effect of hypermedia flipbook on students’ interest and learning outcomes on the material of the VIII grade human excretory system. This study uses a quasi-experimental design research method. The research sample used class VIIIA and VIIIB MTs. Ma’arif Ambulu. In learning outcomes also increased with the results of the analysis 0,000 < 0,005 (Ha accepted). Based on the results of the two analyzes, it shows that flipbook hypermedia can affect students’ interests and learning outcomes.